Soil Phosphorus Dynamics of Wheat-Based Cropping Systems in the Semiarid Region of Argentina - Liliana Suñer; Juan Galantini; Gabriela Minoldo (Applied and Environmental Soil Science)
The dynamics of soil P forms and particle size fractions was studied under three wheat-based cropping sequences in production systems of Argentina. The whole soil and its coarse (100–2000 µm) and fine (0–100 µm) fractions were analyzed to determine Bray-Kurtz extractable (Pe), organic (Po), inorganic (Pi), and total (Pte) phosphorus. The reference soil was determined at time 0 and compared to a four-year period (time 9 to 12) in three crop sequences: wheat (Triticum aestivum L.)-cattle grazing on natural grasses (WG), continuous wheat (WW), and wheat-legume (WL). Levels of Pe showed differences over time, from 10 to 16 µg g−1 in WG, in line with agriculture and cattle grazing alternate sequences. In WW, P level increased with time, while in WL systems a significant decrease in P from 33.7 to 10.4 µg P g−1 was found during the legume period. Soil P values varied between reference soil and soil samples in year nine and between treatments. Pi was significantly lower in WW, and its concentration increased with time. The coarse fraction of the reference plots had significantly higher levels of Po and Pi than the cultivated treatments, probably a consequence of the particulate organic matter decomposition and coarse mineral particle weathering. The observed changes in Pi content could be attributed to differences in occluded P equilibrium under different soil environments (mainly pH) and crop-tillage-climatic interaction.